Vzroki in posledice omejevanja kozjereje v Zgornjem Posočju - Žan, Metka (Etnolog. Nova vrsta (Ljubljana), 2023)
In the past, goat breeding was an important economic activity and an essential source of survival for the inhabitants of Posočje in the Julian Alps. This region was dominated by dairy cattle medium-altitude pasturing communities, but the goats were kept only in higher mountaineous areas of Trenta and Bovec, where the steep and rocky mountain pastures were suitable only for goats, of which there were several thousands. Over the centuries, the only preserved native Slovenian goat breed, the Drežnica goat, was formed there. Goat breeding and grazing were frequently accompanied by legal restrictions, which led to emptying of the mountain villages and a change in the environment. The threat to the Drežnica goat threatens national biodiversity and intangible cultural heritage.
Keywords: drežniška koza; drobnica; koze; kozjereja; kulturna dediščina; ogroženost; pasme; Zgornje Posočje